(untitled) (International journal of medical sciences, 2026)
Benign prostatic hyperplasia is a common urological condition in older men characterized by the excessive growth of glandular and stromal tissues of the prostate. This condition leads to lower urinary tract symptoms such as obstructive and irritative manifestations, including slow urine flow, difficulty initiating urination, frequent urination, nocturia, and occasional urinary incontinence. BPH significantly affects patients’ quality of life, sleep patterns, and daily activities, and may contribute to psychological stress. The pathogenesis of BPH involves complex interactions between hormonal changes, particularly testosterone and dihydrotestosterone, genetic predisposition, inflammatory processes, and impaired microcirculation. Early diagnosis, effective management strategies, lifestyle modifications, and preventive measures are essential to slow disease progression, improve patient outcomes, and reduce the medical and social burden associated with the condition. This study aims to review the etiology, clinical manifestations, diagnostic approaches, and treatment options for BPH while emphasizing the importance of patient-centered care and preventive strategies.